Analyzing the correspondence betwixt the effectiveness of sports clubs and their league Performances in the Moroccan Championship “Botola Pro “ - BENOUZEKRI, Mouad; CHERQAOUI, Mariam (Revue Internationale des Sciences de Gestion, 2023)
The performance of football clubs in Morocco has evolved significantly over the past decade. Given the competitiveness of the market, it’s increasingly necessary to conduct business as companies with corporate models been applied. With the sole goal of winning championships and have successful seasons since these things enable them to earn more money, make investments, and move closer to their objectives. In this regard, the Sporting Indices and the Ranking Performance of the teams in Morocco’s Championship ranking tables for the years 2020 and 2021 were compared in this study. For the purpose of measuring investment performance, Kendall’s data packaging and correlation coefficient analysis were used. There’re multiple teams who has achieved an advanced ranking in the botola league in relation with correlation of their rating in the cost-effectiveness, the results demonstrated a substantial degree of parity in the results over the studied time. So, we concluded that a team’s standing in the championship will improve in direct proportion to how effective it is on the field. The intends is to participate by affirming the necessity of a deep analysis of charges and fundings in order to provide improved results in the search for an effective allocation of resources.